An analysis of spatial market integration: a case of Zambian dry bean markets connected by informal trade to Tanzania and the Democratic Republic of Congo - Sunga, Chalwe (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.